Emotional Intelligence and Work Stress Its Effect on Employee Performance - Wulantika, Lita; Meilani, Siti Nurhaliza; Handayani, T; Al Faruqi , Muhammad Razi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to determine whether there is an effect of emotional intelligence and work stress on employee performance in a financial institution in West Java. This type of research is quantitative. The population in this study were 145 people, the sampling technique used was probability sampling where the number of samples was 59 respondents. Data collection techniques by distributing questionnaires. Data processing is done using SPSS v20. The results of this study indicate that emotional intelligence affects employee performance and this study also shows that job stress affects employee performance. This research may have some limitations, the results are limited to the effect of emotional intelligence and work stress on the performance of employees in a financial institution in West Java. For this reason, further research can be carried out by collecting data using a quantitative or qualitative research approach to certain respondents with different backgrounds.